Bibliometric analysis of published literature on international humanitarian law from Islamic perspective - Elshobake, Mohammed R M; Alashqar, Muath Mohammed (Persatuan Sains Sosial dan Kemanusiaan Muallim, 2024)
Research on International humanitarian law from Islamic perspective in Scopus database was initiated in 1999. Since then, the research on that field has been increasingly used by researcher to examine further issues related to international humanitarian law from Islamic perspective. The objective of this study is to examine the published literature related to the topic of “International Humanitarian Law from Islamic Perspective”. The Scopus database was used to collect all relevant articles. Standard bibliometric analysis was used to offer full information on the increase of publications, research output, and citation analysis. According to research findings, a total of 91 documents were retrieved. It was discovered that the annual growth rate of published material on international humanitarian law from an Islamic perspective has grown since 2016. Most of the articles were published in journals, mainly in English, with the majority of the research on international humanitarian law from Islamic perspective being in the Social Sciences field. “International Humanitarian Law” and “Islamic Law” were the most popular keywords and represent the primary study areas comprised in the topic of international humanitarian law from Islamic perspective. Several research related to the study field was conducted in the United Kingdom and United States. This study shows the development of published literature on international humanitarian law from Islamic perspective, the subjects related to international humanitarian law from Islamic perspective in which researchers are currently interested in, as well as possible directions for future research on the study field.